Loss of SATB2 Expression in Colorectal Carcinoma Is Associated With DNA Mismatch Repair Protein Deficiency and BRAF Mutation. (October 2018) - Ma, Changqing; Olevian, Dane C.; Lowenthal, Brett M.; Jayachandran, Priya; Kozak, Margaret M.; Chang, Daniel T.; Pai, Reetesh K.
Abstract : The special AT-rich sequence binding protein (SATB2) has been reported to be a specific immunohistochemical marker for colorectal carcinoma; however, correlation of SATB2 expression with molecular alterations commonly assessed in colorectal carcinoma has not been performed. We examined the immunohistochemical expression of SATB2 in 586 adenocarcinomas of the gastrointestinal (GI) tract and pancreas to assess its utility in diagnosis and analyze the clinicopathologic and molecular characteristics of colorectal carcinoma stratified by SATB2 expression. SATB2 and CDX2 expression were evaluated in 266 adenocarcinomas of lower GI tract origin (246 colorectal and 20 appendiceal mucinous), 208 adenocarcinomas of upper GI tract and small intestinal origin (74 esophagus/esophagogastric junction, 103 stomach, 20 duodenal, and 11 jejunoileal), and 112 pancreatic ductal adenocarcinomas. SATB2 expression was more frequently identified in adenocarcinomas of lower GI tract origin (222/266, 83%) compared with upper GI tract, small intestinal, or pancreatic origin (26/320, 8%) ( P <0.001). Compared with CDX2 alone, dual positive expression for SATB2 and CDX2 (SATB2 + /CDX2 + ) has a significantly higher specificity for adenocarcinoma of lower GI tract origin (94% vs. 57%, P <0.001). In colorectal carcinoma, loss of SATB2 expression was more frequently observed in DNA mismatch repair (MMR) protein deficient tumors (31%) compared with MMR protein proficient tumors (13%) ( P <0.01). A BRAF V600E mutation was more frequently identified in colorectal carcinomas with loss of SATB2 expression compared with those with positive SATB2 expression (29% vs. 3%) ( P <0.001). In summary, SATB2 expression is a relatively specific marker of lower GI tract origin; however, loss of SATB2 expression is more commonly seen in colorectal carcinoma with MMR protein deficiency and BRAF mutation.